2011
DOI: 10.1016/j.ejogrb.2011.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Duration of passive and active phases of the second stage of labour and risk of severe postpartum haemorrhage in low-risk nulliparous women

Abstract: Conclusion: A prolonged active -but not passive-second stage is associated with the risk of severe PPH in nulliparas. The optimal duration of these phases remains to be defined.-3 -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…To address this issue further, knowledge of the women′s experiences of childbirth before and after our study would have been of major interest and should be a focus of new studies. Long duration of labor and lower maximal dosing of oxytocin are both associated with an increased risk of postpartum hemorrhage . These findings are consistent with our observations and need further attention.…”
Section: Discussionsupporting
confidence: 91%
“…To address this issue further, knowledge of the women′s experiences of childbirth before and after our study would have been of major interest and should be a focus of new studies. Long duration of labor and lower maximal dosing of oxytocin are both associated with an increased risk of postpartum hemorrhage . These findings are consistent with our observations and need further attention.…”
Section: Discussionsupporting
confidence: 91%
“…Another larger registry based study of risk factor for PPH [25] only found a non-significant association with labor lasting >12 hours and severe PPH ≥1500 mL (aOR = 1.9; 95% CI 0.7–5.6). Le Ray et al [18] reported a significantly longer active second stage in women who experienced severe PPH, while no increased risk of PPH was found with a prolonged active first stage. However, their study included only 69 low-risk nulliparous women, representing a subgroup of delivering women.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported that a prolonged second stage of labor is associated with PPH [1416], but previous studies report conflicting results on whether the total duration of active labor increases the risk of PPH. One study looking at the first stage in women with induced labors reported an increased risk of PPH [17], while another study looking at both first and second stage in low-risk nulliparous women reported an association only with the second stage of labor [18]. The International PPH Collaborative Group [19] has recommended that prolonged labor should be among the potential risk factor for PPH investigated in future research.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction of interventions in uncomplicated deliveries is warranted. The risks of complications associated with long duration of active phase of labor such as postpartum hemorrhage have to be weighed against potential adverse effects of augmenting labor with oxytocin such as fetal distress and anal sphincter injuries . Childbirth satisfaction is another important outcome, and in some studies long duration is associated with lower maternal satisfaction , which might lead to cesarean section due to maternal request in later pregnancies.…”
Section: Discussionmentioning
confidence: 99%